Chasing the dime : a novel - Connelly, Michael, 1956- (Boston : Little, Brown, 2002)
After accidentally intercepting some telephone messages for the previous tenant of his new apartment, Henry Pierce is drawn into a web of dangerous secrets as he races against time to save the life of a woman he has never met.
Accelerated Reader AR
Keywords: Telephone answering and recording apparatus -- Fiction; Sex-oriented businesses -- Fiction; Women -- Crimes against -- Fiction; Mystery fiction